2019
DOI: 10.3389/fpsyg.2019.01166
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Facial and Vocal Attractiveness Among College Students in China

Abstract: This study aims to investigate sex differences in ratings for facial attractiveness (FA) and vocal attractiveness (VA). Participants (60 undergraduates in Study 1 and 111 undergraduates in Study 2) rated the attractiveness of computerized face images and voice recordings of men and women. In Study 1, face images and voice recordings were presented separately. Results indicated that men generally rated voice recordings of women more attractive than those of men, whereas women did not show different attractivene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 31 publications
2
7
0
Order By: Relevance
“…Both results indicated that men rated women's voices with higher scores than those women rated men's voices. This is consistent with a recent study which found that men rated other men's voices as less attractive than women's voices whereas women's ratings did not differ for men's voices and women's voices (Hou & Ye, 2019). As women are more sensitive to voice perception than men (Hung & Cheng, 2014) and have advantages over men in terms of speech processing and coding (Hunter, Phang, Lee, & Woodruff, 2005;Schirmer, Striano, & Friederici, 2005;Skuk & Schweinberger, 2013), women are able to more accurately perceive vocal attractiveness.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Both results indicated that men rated women's voices with higher scores than those women rated men's voices. This is consistent with a recent study which found that men rated other men's voices as less attractive than women's voices whereas women's ratings did not differ for men's voices and women's voices (Hou & Ye, 2019). As women are more sensitive to voice perception than men (Hung & Cheng, 2014) and have advantages over men in terms of speech processing and coding (Hunter, Phang, Lee, & Woodruff, 2005;Schirmer, Striano, & Friederici, 2005;Skuk & Schweinberger, 2013), women are able to more accurately perceive vocal attractiveness.…”
Section: Discussionsupporting
confidence: 91%
“…That is, for male raters, the rating for ssOther-by-Self is lower than that for osOther-by-Self; for female raters, the score of ssSelf-by-Self is lower than that of osSelf-by-Self. The former result corroborates previous findings that men rated female voices as more attractive than those of men (Babel et al, 2014;Hou & Ye, 2019). The latter result was associated with the aforementioned strategy that women tend to make themself more attractive in the opposite-sex context.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Considering the results of this systematic review, we can note that there are sex differences in male and female faces and voices [20]. Males prefer more female voices and stimulus.…”
Section: Rq1: How Are Sexbots Designed?mentioning
confidence: 85%